Exploring novel strategies for social media HPV vaccine information. Issue 12 (2nd December 2021) - Thompson, Erika L.; Galvin, Annalynn M.; Garg, Ashvita; Moore, Jonathan D.; Litt, Dana M.
ABSTRACT: To respond to potential public health impacts of social media influencing vaccine confidence, Facebook proposed that prior to proceeding to any link about Human Papillomavirus (HPV) vaccination, a pop-up will prompt the user to visit a reputable website on vaccine information. This study explored the acceptability of a pop-up Facebook message for HPV vaccine information. A national sample of U.S. adults (n = 579) was surveyed online. Most participants rated the pop-up messages as acceptable, useful, and factual. Regression results indicated that being male, seeing HPV content on social media in the past month, believing that information on social media is credible, holding positive HPV vaccination attitudes, and having shared HPV content on their own social media were associated with greater likelihood of clicking on a pop-up. While the pop-up approach may be acceptable, there are many factors that may be associated with being less likely to click on the pop-up.